1985
DOI: 10.1677/joe.0.1070001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flavonoids on insulin secretion and 45Ca2+ handling in rat islets of Langerhans

Abstract: The effects of some flavonoids, a group of naturally occurring pigments one of which has been claimed to possess antidiabetic activities, on insulin release and 45Ca2+ handling have been studied in isolated rat islets of Langerhans. Insulin release was enhanced by approximately 44-70% when islets were exposed to either (-)epicatechin (0.8 mmol/l) or quercetin (0.01-0.1 mmol/l); others such as naringenin (0.1 mmol/l) and chrysin (0.08 mmol/l) inhibited hormone release by approximately 40-60%. These effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(84 citation statements)
references
References 27 publications
3
78
1
2
Order By: Relevance
“…In in vivo studies, diabetic rat models confirmed the insulin-sensitizing effect of dark chocolate. In two such studies, epicatechin increased insulin secretion and regenerated pancreatic β-cells [1315]. Similarly, supplementation of diabetic rats with cocoa extract for four weeks was dose-dependently associated with reduced serum glucose, post-prandial hyperglycemia, atherogenic lipid levels, insulin resistance, and 8-isoprostane, a biomarker of oxidative stress [1417].…”
Section: Positive Effectsmentioning
confidence: 99%
“…In in vivo studies, diabetic rat models confirmed the insulin-sensitizing effect of dark chocolate. In two such studies, epicatechin increased insulin secretion and regenerated pancreatic β-cells [1315]. Similarly, supplementation of diabetic rats with cocoa extract for four weeks was dose-dependently associated with reduced serum glucose, post-prandial hyperglycemia, atherogenic lipid levels, insulin resistance, and 8-isoprostane, a biomarker of oxidative stress [1417].…”
Section: Positive Effectsmentioning
confidence: 99%
“…Vessal et al (2003) reported that supplementation has proven to be beneficial in decreasing the concentration of blood glucose, promoting the pancreatic islets regeneration and increasing release of insulin in STZ treated diabetic rats; thus exerting its beneficial antidiabetic effects (Formica and Regelson 1995). This is supported by the previous literature reports where these types of flavonoids enhance release of insulin up to 70% by its effect on function of islet at least in part, metabolism of cyclic nucleotide, and via alteration in Ca +2 fluxes (Yen et al, 2009;Hii and Howell, 1985a;Hii and Howell, 1985b). Blood glucose levels were significantly increased after 72 h following STZ injection compared to control group, while all QUE treatment groups had significantly decreased blood glucose concentrations compared to the diabetic group after 30 days (Elbe et al, 2015).…”
Section: Effect Of Qunps On Blood Sugars Urea Creatinine and Uric Acidmentioning
confidence: 65%
“…Flavonoids are reported to possess antidiabetic activity as they can preserve β-cell function and prevent diabetes induced ROS formation (Aslan et al, 2007). Moreover, Hii and Howell (1985) mentioned that certain flavonoids enhanced insulin release from the isolated rat islets. Thus, the hypoglycemic effect of F. drudeana and F. huber-morathii may be due to the presence of flavonoids.…”
Section: Discussionmentioning
confidence: 99%